The Role of Vitamin D in Preventing Acute Respiratory Tract Infections in Children: Literature Review - Christie July Prawatya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Acute Respiratory Tract Infections (ARI), particularly pneumonia, are a leading cause of death in children under five years of age globally and in Indonesia. Vitamin D, in addition to its important role in bone health, has immunomodulatory functions by increasing the production of antimicrobial peptides such as cathelicidin and defensin, and suppressing excessive inflammatory responses. This literature review aims to explore the potential role of vitamin D supplementation in preventing ARI in children, focusing on innate and adaptive immune mechanisms, factors influencing its effectiveness, and current clinical evidence. Literature searches were conducted using PubMed, Scopus, the Cochrane Library, and Google Scholar with the following keywords “acute respiratory tract infection”, “children”, “pediatric”, “pneumonia”, “vitamin D”. The search was limited to publications from 2015–2025. A total of 356 articles were identified, of which 72 were screened based on title and abstract. After full-text eligibility assessment, 6 articles met the inclusion criteria and were included in this review. Articles were critically appraised by examining study design, sample size, intervention (dose and duration of vitamin D), and outcomes measured. Data were synthesized narratively to compare findings across studies. This review shows that vitamin D supplementation, especially in children with low baseline levels (<25 ng/mL), can reduce the incidence and duration of ARI, with a more pronounced protective effect in high-risk groups. Effectiveness is influenced by baseline vitamin D status, dose, duration of administration, age, and sunlight exposure. Clinically, these findings support the recommendation of monitoring vitamin D levels and providing supplementation as a significant preventive strategy to reduce the burden of acute respiratory infections (ARI) in children.